Upaya Penanganan Stres Melalui Kecerdasan Spiritual Pada Mahasiswa - Nurfajrin, Deva; Nasichah; Isnaini, Zahrah; Ardila, Syifa (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2023)
Stress often occurs among students, this is caused by prolonged academic, social and emotional pressure. This results in decreased mental health conditions. This research aims to find out in depth how students are able to overcome their stress through spiritual intelligence, especially students with the UIN Jakarta Islamic Counseling Guidance study program in improving their overall mental health. The research method used is a descriptive qualitative method with data collection techniques in the form of interview techniques. The subjects in this research were students of the Islamic Counseling Guidance study program at UIN Syarif Hidayatullah Jakarta, consisting of 5 participants. The results of the research reveal that Islamic Counseling Guidance students have implemented stress management through spiritual intelligence. They admit that spiritual intelligence can help them feel calmer and can manage stress well in facing various challenges in everyday life.